Examining the Relationship between Exercise Dependence, Disordered Eating, and Low Energy Availability - Megan A. Kuikman (Nutrients, 2021)
Both dietary and exercise behaviors need to be considered when examining underlying causes of low energy availability (LEA). The study assessed if exercise dependence is independently related to the risk of LEA with consideration of disordered eating and athlete calibre. Via survey response, female (n = 642) and male (n = 257) athletes were categorized by risk of: disordered eating, exercise dependence, disordered eating and exercise dependence, or if not presenting with disordered eating or exercise dependence as controls. Compared to female controls, the likelihood of being at risk of LEA was 2.5 times for female athletes with disordered eating and >5.5 times with combined disordered eating and exercise dependence. Male athletes with disordered eating, with or without exercise dependence, were more likely to report signs and symptoms compared to male controls-including suppression of morning erections (OR = 3.4; p < 0.0001), increased gas and bloating (OR = 4.0–5.2; p < 0.002) and were more likely to report a previous bone stress fracture (OR = 2.4; p = 0.01) and ≥22 missed training days due to overload injuries (OR = 5.7; p = 0.02). For both males and females, in the absence of disordered eating, athletes with exercise dependence were not at an increased risk of LEA or associated health outcomes. Compared to recreational athletes, female and male international caliber and male national calibre athletes were less likely to be classified with disordered eating.